Development of a time/temperature logging device to characterise the burning characteristics of biofuels - Smit, Hendrik Christiaan (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2011.